Institutionalization of Political Parties on Post New Order Authoritarianism and It’s Implications for Indonesian Democracy - Laode Muliawan; Imam Sumantri (Universitas Muhammadiyah Malang, 2020)
The article is focused on explaining how institutionalization of political parties in Indonesia after the collapse of New Order regimes and how it affects democratization in Indonesia. It is considered important since Soeharto’s regime rose to power, political parties are being forced to limit their ideal function/ In this article, the writers concludes that political parties in Indonesia after the authoritarianism regime, have not been institutionalized and are even far from it if compared to the magnitude level its current problem. Political parties are trapped on long term internal conflict of interest, drained their energy and still continued until now. Moreover, the depth oligarchies pattern in its management is worsened by personalized figure and the dominance of party’s management from the central, forced us into the conclusion that political party are just the sub-ordinates of elite’s interest. The result, political parties are simply failed to play important role in supporting consolidated democracy, since they are busy and distracted by their own internal problems. That’s why, when will Indonesia rise into transition phase in democracy is still questionable, especially if the question is solely based on institutionalization of political parties.